Denmark : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Denmark. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights the recovery of the Danish economy, which is approaching potential, despite growth in recent years that has been markedly slower than before the crisis. Unemployment is low and close to its estimated structural level, and capacity constraints are gradually starting to bind in some sectors. The coincidence of low output growth and increasingly binding constraints highlights Denmark's reduced growth potential, reflecting structurally weak productivity growth and low domestic investment levels. The outlook is for continued moderate growth, projected at 1.5 percent in 2017 and 1.7 percent in 2018. Activity is expected to be driven by strong and increasingly balanced private demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet